Comparative Efficacy and Safety of 11 Drugs as Therapies for Adults With Neuropathic Pain After Spinal Cord Injury: A Bayesian Network Analysis Based on 20 Randomized Controlled Trials - Ling, Hai-Qian; Chen, Zi-Hao; He, Lei; Feng, Feng; Weng, Chuang-Gui; Cheng, Si-Jin; Rong, Li-Min; Xie, Pei-Gen (Frontiers in Neurology, 2022)
Objective: To provide an updated analysis of the efficacy and safety of drugs in the management of neuropathic pain (NP) after spinal cord injury (SCI) based on Bayesian network analysis. Methods: We conducted a Bayesian network meta-analysis whereby the subject words and free words were used for literature search for articles in PubMed, Cochrane Library, Embase, and Web of Science from their inception to June 21, 2020, and updated on February 21, 2021, without language restrictions. Paired and network meta-analyses of random effects were used to estimate total standardized mean deviations (SMDs) and the odds ratios (ORs). Results: We identified 1133 citations and eventually included 20 RCTs (including 1198 patients) with 11 drugs and placebo for NP after SCI. Based on Bayesian network analysis, 5 outcomes of all 11 drugs and placebo had no inconsistency. In terms of the pain relief for 4 weeks of the primary outcome, BTX-A was taken as the most effective drug. With regards to any adverse events of the primary outcome, most drugs showed no significance between each other. From the secondary outcome of efficacy, gabapentin, BTX-A, and pregabalin were found to be more helpful in relieving mental or sleep-related symptoms, with differences in SMDs ranging from -0.63 to -0.86. Whereas for safety, tramadol triggered more serious adverse events than any of the other active drugs with differences in ORs ranging from 0.09 to 0.11. Conclusions: In the management of NP after SCI, BTX-A, gabapentin, pregabalin, amitriptyline, ketamine, lamotrigine, and duloxetine were shown to be favorable. Lamotrigine and gabapentin, in particular, showed fewer side effects and better efficacy in relieving mental or sleep-related symptoms caused by SCI-related NP. However, tramadol, levetiracetam, carbamazepine, and cannabinoids were not recommended due to their inferior safety or efficacy.